Zabezpieczenia finansowe jako przejaw odpowiedzialności w ochronie środowiska na przykładzie składowiska odpadów komunalnych - Ciechelska, Agnieszka (Financial protection as environmental responsibility on the example of communal waste disposal, 2007)
The Polluters Pay Principle is used in Polish law system and accommodates for the fmancial protection of victims of potential environmental damages. According to Polish environmental law such fmancial protection can be in the form of bank guarantee, bank deposit, or environmental insurance. The fmancial protection applies only to given activity and it is in the form of administrative decision. Situations when protection can be used or retumed are also defined in Polish environmental law. The problem lies in how to estimate the protection sum. There are no acts controlling this issue. In this article the author tries to define the methodology of identification and evaluation of potential environmental damages using the example of communal waste disposal. Such methodology should be mainly based on environmental risk assessment. Although fmancial protection is obligatory it is not used in practice. The reason of this is connected with weak offer in fmancial sector (only environmental deposit) and insufficient defmition of evaluation damages methodology. That is why further research in this field is necessary.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 434-449